No 4 (2020): Homenaje a La Profesora Carmen Fernández Ochoa 2020
DOI: 10.15366/ane4.ochoa2020.005
|View full text |Cite
|
Sign up to set email alerts
|

Las estelas de guerrero del valle medio del Tajo. Recreación experimental del proceso de elaboración

Abstract: Presentamos los resultados de la recreación experimental de una estela de guerrero utilizando como modelos seis estelas del Valle Medio del Tajo: Las Herencias I, Arroyo Manzanas (o Las Herencias II) y Barranca del Águila (Talavera de la Reina) en la zona norte, próximas al río Tajo, así como las dos de Aldeanueva de San Bartolomé y La Estrella en la comarca de la Jara. La réplica se ha elaborado a lo largo de 4 horas con cinceles de bronce sobre una losa rectangular de esquisto grauváquico procedente de la Ja… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 8 publications
0
2
0
1
Order By: Relevance
“…Johan Ling) to produce and disseminate high resolution digital recordings of warrior stelae (at least 100), and compare them (including their manufacture) with Scandinavian rock art. Secondly, between 2019 and 2021 various key papers have been published reporting on the results of new replication experiments exploring the manufacture of warrior stelae from the upper Tagus valley with metallic tools (Gutiérrez et al, 2020), and offering new insights on the manufacture techniques and chaîne opératoire of warrior stelae obtained through the application of digital technologies (García-Arilla et al, 2021;Díaz-Guardamino et al, 2019;2020); other papers explore some of the theoretical implications of those tecnological findings (Díaz-Guardamino, 2020; 2021). Fi-nally, in 2020 another project was granted to Ralph Araque, The Iberian stelae of the Final Bronze Age: iconography, technology and the transfer of knowledge between the Atlantic and the Mediterranean (2021-23), funded by the DFG.…”
Section: Iberian Late Bronze Age Warrior Stelae: From Iconography To ...mentioning
confidence: 99%
See 1 more Smart Citation
“…Johan Ling) to produce and disseminate high resolution digital recordings of warrior stelae (at least 100), and compare them (including their manufacture) with Scandinavian rock art. Secondly, between 2019 and 2021 various key papers have been published reporting on the results of new replication experiments exploring the manufacture of warrior stelae from the upper Tagus valley with metallic tools (Gutiérrez et al, 2020), and offering new insights on the manufacture techniques and chaîne opératoire of warrior stelae obtained through the application of digital technologies (García-Arilla et al, 2021;Díaz-Guardamino et al, 2019;2020); other papers explore some of the theoretical implications of those tecnological findings (Díaz-Guardamino, 2020; 2021). Fi-nally, in 2020 another project was granted to Ralph Araque, The Iberian stelae of the Final Bronze Age: iconography, technology and the transfer of knowledge between the Atlantic and the Mediterranean (2021-23), funded by the DFG.…”
Section: Iberian Late Bronze Age Warrior Stelae: From Iconography To ...mentioning
confidence: 99%
“…Prominent among this is the fact that direct pecking does provide equal control and requires less time than indirect pecking (Whittaker et al, 2000: 165-66), inviting us to reconsider the traditional pre-eminence given by researchers to the latter (e.g. Gutiérrez et al, 2020). But, above all, this experiment revealed that petroglyph making does not require a huge effort, neither 'exoteric technical skills, and rarely if ever cost much in terms of either labour or resources' (Whittaker et al, 2000: 166;see also García Sanjuán et al, 2006: 143-44).…”
Section: Stelae Carving Replication Experimentsmentioning
confidence: 99%
“…Sus resultados podrán consultarse en la web https://www. experimentalarchaeology.uni-freiburg.de/ Dentro de este apartado debemos incluir la experiencia en la elaboración de estelas llevadas a cabo en el Laboratorio de Arqueología Experimental de la Universidad Autónoma de Madrid, en las que se abordan los posibles instrumentos y las técnicas concretas utilizadas (Gutiérrez et al 2020). Podemos resaltar tres elementos de la experiencia realizada: la rapidez y relativa sencillez a la hora de realizar la estela, las marcas generadas por la talla y los restos del instrumental de bronce empleado conservados en la pieza.…”
Section: Técnicas De Grabado E Instrumentalunclassified